Hymenoptera: A Quick Review (Homoeopathy for All, 2022)
Hymenoptera is an order of insects  including bees, wasps and ants  characterized by locked pairs  of membranous wings and high  development of social or colonial  behavior. Man had started the use  of insects and insect products since  ancient time. Hymenoptera deals  with some important and very  useful homoeopathic medicines  like Apis mellifica, Formica rufa  and Vespa crabro.
Keywords: Hymenoptera; Apis mellifica; Formica rufa; Vespa crabro